2018
DOI: 10.18632/oncotarget.23985
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery disease risk in young women with polycystic ovary syndrome

Abstract: Women with polycystic ovary syndrome are characterized by obesity, menstruation irregularity, hirsutism and infertility, and prevalent with cardiometabolic comorbidities, but population-based studies on the risk of developing coronary artery disease are limited. From claims data of the Taiwan National Health Insurance, we identified 8048 women with polycystic ovary syndrome aged 15-49 years newly diagnosed in 1998-2013, and 32192 women without the syndrome and CAD as controls, frequency matched by age and diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 39 publications
0
28
0
Order By: Relevance
“…Search results Figure 1 presents the search strategy and study selection. Of 5236 records retrieved through searching databases 30 studies including 17 population based [2,3,7,19,[34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] and 11 non-population based studies [4,5,10,34,[49][50][51][52][53][54][55][56] were selected for the final analyses. Twenty-four studies assessed a population of reproductive age patients with PCOS [2, 3, 5, 7, 10, 34-38, 40, 41, 43-47, 49-51, 53-56], 4 studies-menopausal/aging women [19,39,52,57], and two studies-both age groups of patients (reproductive and menopausal/aging women) [4,48].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Search results Figure 1 presents the search strategy and study selection. Of 5236 records retrieved through searching databases 30 studies including 17 population based [2,3,7,19,[34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] and 11 non-population based studies [4,5,10,34,[49][50][51][52][53][54][55][56] were selected for the final analyses. Twenty-four studies assessed a population of reproductive age patients with PCOS [2, 3, 5, 7, 10, 34-38, 40, 41, 43-47, 49-51, 53-56], 4 studies-menopausal/aging women [19,39,52,57], and two studies-both age groups of patients (reproductive and menopausal/aging women) [4,48].…”
Section: Resultsmentioning
confidence: 99%
“…Androgen excess in PCOS may also directly influence the vascular properties of arterial walls and the expression of molecules involved in the atherogenic process [60]. However, contrasting results on the prevalence of hypertension in PCOS have been reported by some studies suggesting increased prevalence [3,7,35,36,38,40,41,43], whereas others find no significant differences in general populations [2,19,39,42,[44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that almost all cardiovascular risk factors including IR, diabetes mellitus (DM), dyslipidemia, obesity, hypertension, and metabolic syndrome are associated with PCOS (4)(5)(6)(7)(8). These risk factors are present even in young patients with PCOS and predispose to the development of endothelial dysfunction, early atherosclerosis and cardiovascular disease (CVD) (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Polycystic ovary syndrome (PCOS) is a common reproductive endocrine disease characterized by menstrual disorder, oligo/anovulation, hyperandrogenemia, polycystic ovaries, and insulin resistance. [ 1 ] Studies [ 2 , 3 ] show that PCOS with complex etiology affects 6% to 15% women of childbearing age, approximately 75% of whom experience infertility due to anovulation. The pathogenesis of PCOS is mostly metabolic disorder caused by insulin resistance and secondary hyperinsulinemia, which can lead to endometrial cancer, cardiovascular disease, type 2 diabetes, and other diseases over time, affecting women's physical, and mental health.…”
Section: Introductionmentioning
confidence: 99%